The Relationship of Parenting Patterns with Discipline Class XI Students Learning in MAN 3 Padang City - Gusriadi Nadilla, Nadilla; Yulastri, Weni; Kardo, Rici (Jurnal Riset Ilmu Pendidikan, 2022)
This research is motivated by the lack of student learning discipline. The purpose of this study is to describe: 1) Student learning discipline. 2) Parenting style. 3) The relationship between parenting styles and students' learning discipline. This type of research is descriptive quantitative research, with a population of 313 students and a sample of 76 students. The sampling technique used is simple random sampling. The research instrument was a questionnaire and analyzed using the percentage technique. The results of this study reveal that 1) The learning discipline of students is in the high category, 2) The parenting style of parents is in the high category, 3) There is a significant relationship between parenting and learning discipline with a correlation coefficient of 0.547 with a strong level of relationship. Based on the results of the study, it can be recommended for parents to further improve learning discipline, especially in asking children which major is better in the future so that they can provide proper treatment to their children.